Postnatal Mental Health, Hand Washing Practices, and Infant Illness in Rural China - Jiang, Qi; Cohen, Nourya; Ohtori, Mika; Gao, Jie; Wang, Qingzhi; Zhang, Evelyn; Zhu, Sabrina; Johnstone, Hannah; Guo, Yian; Dill, Sarah-Eve; Zhou, Huan; Rozelle, Scott (Frontiers in Global Women's Health, 2021)
Background: Maternal mental health problems play an important role in infant well-being. Although western countries have extensively studied the associations between maternal mental disorders, hygiene practices and infant health, little is known in developing settings. This study investigates the correlations between postnatal mental health problems, hand washing practices and infant illness in rural western China. Methods: A total of 720 mothers of infants aged 0–6 months from four poor counties in rural western China were included in the survey. Mental health symptoms were assessed using the Depression, Anxiety, and Stress Scale-21 (DASS-21). Questions about infant illness and hand washing practices followed evaluative surveys from prior studies. Adjusted ordinary least squares regressions were used to examine correlations between postnatal mental health (depression, anxiety, and stress) symptoms, hand washing practices, and infant illness outcomes. Results: Maternal depression, anxiety and stress symptoms were significantly associated with reduced hand washing overall and less frequent hand washing after cleaning the infant's bottom. Mental health symptoms were also associated with a higher probability of infants showing two or more illness symptoms and visiting a doctor for illness symptoms. Individual hand washing practices were not significantly associated with infant illness; however, a composite measure of hand washing practices was significantly associated with reduced probability of infant illness. Conclusion: Postnatal mental health problems are prevalent in rural China and significantly associated with infant illness. Policy makers and practitioners should investigate possible interventions to improve maternal and infant well-being.